Insurgency in Pakistan and the Government’s Strategic Policies in Dealing with it - Pertiwi, Yuliana Anggun; Tatara, Beny A.; Margiati, Titis; Mujib, Syahrir (PT FORMOSA CENDEKIA GLOBAL, 2024)
Pakistan is one of the countries in the South Asian region with a complicated insurgency threat. The marginalization carried out by the government against certain groups is the main trigger for the emergence of separatist groups that oppose political authority. In its development, the group mutated to become a very large and brutal population. This study will analyze the description of the insurgency threat that occurred in Pakistan and how the government's strategy in dealing with the insurgency threat is. This research was conducted using a descriptive approach, with research data obtained from primary data and secondary data. In this study, the researcher concludes that the threat of insurgency in Pakistan is very complex and tends to last a long time, because past grievances have not been resolved and the interests of many separatist groups conflict with each other, thereby prolonging the asymmetrical conflict in Pakistan. Facing the threat of insurgency, the Pakistani government uses a military and non-military approach as well as seeks to strengthen national defense to be able to reduce conflicts that occur and minimize the impact caused by the long-standing insurgency conflict